The impact of training on the use of electronic health records - Devkota, B; Lamia, JF; Pommer, N; Smith, J; Whitman, B (Health Renaissance, 2011)
Background: Studies have found that health information technology can improve the quality and efficiency of care delivery through better decision support. Objective: To gauge the effectiveness of electronic health records (EHR) training that was delivered to health care providers in an academic practice, to leverage feedback from the training evaluation to inform the content and process of training health care providers and to understand the impact of EHR implementation on all facets of health care delivery. Methods: A mixed methods instrument was designed to assess learning outcomes (cognitive, attitudinal and behavioral) associated with EHR training. A sample of 220 health care providers who regularly interacted with the EHR system was included. Participants were asked to evaluate cognitive, attitudinal, and behavioral aspects of their training with the EHR system. A multidimensional assessment of learning outcomes was selected. Results: On behavioral theme, 50% of our survey respondents answered the questions positively, 28% did not, 16% had mixed feelings, 3% felt EHR had negative impacts and 3% were neutral. On cognitive theme 31% felt EHR had a positive impact, 33% felt it had drawbacks whereas 35% left the answers blank and 1% felt they had no idea. On attitudinal theme, there was positive response from 45%, 21% had negative feelings about the system, 5% were neutral and the rest 25% did not answer. Conclusions: In this study, we found that majority of the respondents were satisfied with the EHR for behavioral and attitudinal themes. Future studies with mandatory response to cognitive theme will help figure out the satisfaction of survey respondents on all themes. DOI: http://dx.doi.org/10.3126/hren.v9i3.5580 HR 2011; 9(3): 140-147